PENERAPAN PROGRAM ENTREPRENEURSHIP DI MA ENTREPRENEUR MANBA’UL HUDA DALAM PERSPEKTIF PENDIDIKAN ISLAM TAHUN PELAJARAN 2021/2022 - Dian Rustya; Wahid Anwar (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
The problem of this research is to explain the Implementation of the Entrepreneurship Program at MA Entrepreneur Manba'ul Huda in the Perspective of Islamic Education for the 2021/2022 academic year. The theories used as a foundation in the implementation of this research include the theory of the basis of entrepreneurship and the theory of Islamic education. Based on the background of the problem, this research is expected to provide answers to the formulation of the problem (1) How is the implementation of the entrepreneurship program at MA Entrepreneur Manba'ul Huda for the 2021/2022 academic year? (2) How is the entrepreneurship program in the perspective of Islamic Education? Based on the formulation of the problem, this study aims (1) To find out the implementation of the entrepreneurship program at MA Entrepreneur Manba'ul Huda in the 2021/2022 academic year. (2) To find out the entrepreneurship program in the perspective of Islamic Education. This research uses a qualitative descriptive method and is a type of qualitative research with a case study research approach (case study), Qualitatively is to process and analyze the data that has been collected through interviews, observation and documentation methods. The research subjects were MA Entrepreneur Manba'ul Huda class X students totaling 26 students. Data collection techniques through interviews and questionnaires given to students. From the results of the study it can be concluded that the application of entrepreneurship programs carried out in MA Entrepreneurship Manba'ul Huda there are 3 programs, namely 1. Entrepreneurship subject program 2. MHC (Manba'ul Huda Creative) 3. Industrial visits (study tour). This program aims to introduce entrepreneurial values and foster entrepreneurial characters in students. As well as the entrepreneurship program at MA Entrepreneurship Manba'ul Huda teaches the values of discipline, independence, realistic, commitment and honesty that are in accordance with Islamic education sourced from the Qur'an and As-Sunnah.